Correction: Highly efficient room-temperature phosphorescence achieved by gadolinium complexes. Issue 5 (22nd January 2020) - Sun, Boxun; Wei, Chen; Wei, Huibo; Cai, Zelun; Liu, Huanyu; Zang, Zhiyu; Yan, Wenchao; Liu, Zhiwei; Bian, Zuqiang; Huang, Chunhui
Abstract : Correction for 'Highly efficient room-temperature phosphorescence achieved by gadolinium complexes' by Boxun Sun et al., Dalton Trans., 2019, 48, 14958–14961.